Estudo de aproveitamento de rejeito de mineração - Ana Claudia Franca Gomes (2016)
The greatest and noblest challenge of mining engineering for the present and the future of the treatment of iron ore could be considered as the pursuit of optimizing the use of the mineral resources. The need for obtaining adequate places for tailings disposal, reducing waste volumes sent to the tailings dams associated with the growing difficulty in obtaining environmental licenses, are some of the factors that make the processing of slimes a real alternative for increasing the iron and mass recoveries. In order to investigate said scenario, a technological characterization of the sample from the tailing dam was carried out along with magnetic sorting tests to propose a likely concentration route. The literature elucidated successful recuperation of fine iron particles in mines on the Quadrilátero Ferrífero; in all cases, the technical evaluation was essential. In relation to the characterization itself, the results demonstrated a relative density of 3,04g/cm³ and an average SBET above the range of 38m from the 3,75cm³/g. The granulometric analysis classified the material as fine, with d90 of 75m, 30% inferior to 38m and 5% below 10m. The quartz, hematite, goethite, kaolinite and manganese oxide were identified and the Jones-type high-intensity magnetic separator presented the best overall results within the tested equipment. The dispersion analysis indicated that both a rise in pH as well as the addition of dispersant increased the suspensions dispersion degree and the selectivity during the magnetic separation. The maximum values were identified for a 900 g/t of hexametaphosphate and sodium polyacrylate and pH 9,5. As for the magnetic sorting tests executed with the Jones-type sorter, in general it can be said that the greater the selectivity for the concentrate, the smaller its recuperation will be. A greater release, dispersion, washing pressure and dilution of the pulp promotes a richer concentrate. Among the aforementioned tests, the ones which presented the best results (65,91% Fe and 2,70% SiO 2) were done in this equipment with the Rougher, Cleaner, Recleaner and Scavenger phases, a 1.5mm grooved GAP matrix, a 10,000 G magnetic field, 30% solid, 2 and 1L of water pressure at 0.5 kgf/cm and with the addition of sodium hexametaphosphate (900g/t). Finally, the conclusive results indicate that the studied material can be concentrated through magnetic sorting, keeping in mind the specifications concerning the pellet feed fines commercial product. Besides the financial gain, the activity prolongs the durability of the tailing dam and reduces the environmental impacts associated with these structures.